The Management of Hysteroscopy Complications - Ayla Eser; İlknur İnegöl Gümüş; Ebru Yüce; Nilüfer Akgün; Müberra Namlı Kalem (Gynecology Obstetrics & Reproductive Medicine)
Gynaecological endoscopic procedures such as hysteroscopy and laparoscopy have a good safety profile, with advantages such as decreased hospital stay, reduced complications, reduced operative procedure time and improved recovery time. However like any surgical procedure hysteroscopy is not completely risk-free. General incidence of complications for diagnostic and operative hysteroscopic procedures is low. Overall complication rate is 2% and a major complication rate is 1%. Training and supervision of new surgeons, familiarity with equipment and instruments, development of excellent surgical skills and awareness of potential complications are keys to management of complications in gynaecological endoscopic procedures. These include use of newer types of surgical instruments such as smaller-diameter hysteroscopes, pharmacological adjuvants and materials including hyaluronan gels such as Hyalobarrier®. Complications and the techniques and innovations that are used or are being developed to minimise and manage them are discussed in this literature review.